Between art and anthropology contemporary ethnographic practice - Schneider, Arnd 1960-; Wright, Christopher (Christopher J.) (Berg Publishers, 2010)
"Between Art and Anthropology provides new and challenging arguments for considering contemporary art and anthropology in terms of fieldwork practice. Artists and anthropologists share a set of common practices that raise similar ethical issues, which the authors explore in depth for the first time. The book presents a strong argument for encouraging artists and anthropologists to learn directly from each other's practices 'in the field'. It goes beyond the so-called 'ethnographic turn' of much contemporary art and the 'crisis of representation' in anthropology, in productively exploring the implications of the new anthropology of the senses, and ethical issues, for future art-anthropology collaborations. The contributors to this exciting volume consider the work of artists such as Joseph Beuys, Suzanne Lacy, Marcus Coates, Cameron Jamie, and Mohini Chandra. With cutting-edge essays from a range of key thinkers such as acclaimed art critic Lucy R. Lippard, and distinguished anthropologists George E. Marcus and Steve Feld, Between Art and Anthropology will be essential reading for students, artists and scholars across a number of fields"--Provided by publisher.